(untitled) (Innovation & Development in Engineering and Applied Science, 2024)
The objective of this study is to illustrate the design of a microgrid based on photovoltaic solar energy, considered a clean energy source, aimed at supplying a specific marginal urban area. The mechanism employed involves the integration of alternative technologies or renewable energies with conventional energy system technologies. This work emphasizes the concepts utilized, the advantages, and the challenges faced on a day-to-day basis in these areas. The data for this study were obtained from a meteorological station, enabling the recording of various parameters such as temperature, radiation, among others. This process resulted in the acquisition of historical temperature data, both maximum and minimum. The information obtained was processed using the PVsyst software, which facilitated the selection of photovoltaic modules and their inverter. Additionally, economic feasibility was assessed in the context, utilizing indicators such as Net Present Value (VAN) and Internal Rate of Return (TIR)